The sensitivity analysis of the change in oil price on Norwegian government budget in years 2005-2015 - Yarova, Hanna; Pekárek, Štěpán; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
This study selectively surveys, unifies and extends the literature on the volatility of prices on commodity goods, in particular oil and its effect on the government budget of Norway in the period from 2005 until 2015. It employs an analytic framework that examines the sensitivity of the economical channels that connect the government budget of Norway to the offshore economy. Data was gathered from the reports provided by the Ministry of Finance, Statistics Norway and Norges Bank. Findings suggest that oil price is an important factor affecting the government revenues and expenditures and that from the assesses channels only the channel of Government Pension Fund Global in Norway is the least sensitive to fluctuation in the oil prices.
Vedoucí práce: Štěpán Pekárek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses